Size-exclusion chromatography as a multi-attribute method for process and product characterization of adeno-associated virus - Sri Hari Raju Mulagapati; Arun Parupudi; Tomasz Witkos; Nick Bond; Xiaoyu Chen; Thomas Linke; Guoling Xi; Albert Ethan Schmelzer; Wei Xu (Molecular Therapy: Methods & Clinical Development)
Adeno-associated viruses (AAVs) have recently emerged as a leading platform for gene therapy. Due to the complex manufacturing process and structural features of AAVs, extensive process and product characterization studies are required to better understand product quality and batch-to-batch variability. It is, therefore, critical to develop a fast and reliable analytical method to monitor different product quality attributes (PQAs) of AAVs. In this study, we developed a multiple-attribute monitoring (MAM) method for the characterization of AAV PQAs. The MAM method was developed using the separation capability of size-exclusion chromatography (SEC) in connection with multiple in-line detectors: ultraviolet (UV), fluorescence (FLD), multi-angle light scattering (MALS), and refractive index (RI). We demonstrate that our SEC-based MAM method can be used to measure different PQAs, including genome and capsid titer, purity, aggregation, and full/empty capsid ratios in a single assay. Our SEC-based MAM method achieves similar results when compared side by side with orthogonal, individual assays such as quantitative polymerase chain reaction (qPCR), enzyme-linked immunosorbent assay (ELISA), and anion-exchange chromatography (AEX). Moreover, here we demonstrate that a simple, label-free, cost-effective, minimum sample requirement, and a high-throughput method can be applied to support process development, product characterization, release, and stability testing.